The relationship between women earning potential, financial need, household responsibilities and workplace environment towards women work-life conflicts at Pejabat Daerah Dan Tanah Temerloh, Pahang / Aimi Noridayu Fitrah Ab Wahab - Ab Wahab, Aimi Noridayu Fitrah (Faculty of Business and Management, 2019)
The final report project was carried out in order to fulfill the requirement of the Academic Project (ASM662). The study will be conducted at the government organizations at Pahang. There are four main objectives are to identify the relationship between women earning potential and women work-life conflict, to identify the relationship between financial need and women work-life conflict, to identify the relationship between household responsibilities and women work-life conflict and to identify the relationship between workplace environment and women work-life conflict. By referring to Krejcie and Morgan table (1970), the scopes are focused on the certain number of population. The number of sample size is 63 of respondents. The sampling technique used is simple random sampling. The data will be analyzed and interpreted using SPSS software. It is hope that from the overall findings, we could discover that employees at Pejabat Daerah dan Tanah Temerloh, Pahang specifically women to have work-life conflict at the office. The employees able to know more about the work-life conflict which is in women earning potential, financial need, household responsibilities and workplace environment. It is hope that the more significant it is toward handling the issues among them.